Advances in measuring soil organic carbon stocks and dynamics at the profile scale - Poeplau, Christopher (Burleigh Dodds Series in Agricultural Science, 2023)
Accurate estimation of soil organic carbon (SOC) stocks and dynamics along the soil profile is challenging due to the immense diversity and complexity of soils leading to the spatio-temporal variability of the parameters of interest. It is conducted in a wide range of different frameworks with diverse conceptual and analytical approaches. Our purpose in this chapter is to give a broad overview on methods for monitoring, reporting and verifying SOC stocks and their dynamics. This includes sampling and sensing techniques, SOC stock calculation, as well as SOC fractionation and assessment of SOC turnover along the soil profile using stable isotopes and alternative approaches. It is highlighted that certain key operational challenges need to be overcome for the determination of bulk SOC stocks and changes. Some of these issues, e.g. the depth vs. mass-based comparisons were discussed for several decades, while others have been less addressed so far.